2010
DOI: 10.1016/j.otohns.2010.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharyngeal packing during nasal surgery on postoperative nausea and vomiting

Abstract: Pharyngeal packing in nasal surgery has no impact on PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 24 publications
2
55
2
1
Order By: Relevance
“…It suggested that further studies be done to confirm best practice techniques . Since that time, two prospective, randomized, controlled, double‐blinded studies have been published in the literature . Both studies concluded that pharyngeal packs have no effect on pain or PONV.…”
Section: Introductioncontrasting
confidence: 98%
See 3 more Smart Citations
“…It suggested that further studies be done to confirm best practice techniques . Since that time, two prospective, randomized, controlled, double‐blinded studies have been published in the literature . Both studies concluded that pharyngeal packs have no effect on pain or PONV.…”
Section: Introductioncontrasting
confidence: 98%
“…However, the authors concluded that postoperative pain was higher in the pharyngeal pack group. This was in contrast to the findings of Korkut et al and Fennessey et al that there was no difference in pain between the groups. A major weakness to the Iranian study is that the authors included a variety of otolaryngologic surgeries and not just FESS.…”
Section: Introductioncontrasting
confidence: 98%
See 2 more Smart Citations
“…[34] Apart from the common surgical complication such as bleeding, orbital trauma, intracranial injury and infection, various other complications like aspiration, embolism, nausea and vomiting, myocardial infarction, airway edema and obstruction can also arise. [567891011] The obstructive component can be severe at times leading to re-intubation for maintaining patency of airway. Normally the mechanism of breathing is a very complex phenomenon which is hardly perceived during the routine daily chores.…”
Section: Introductionmentioning
confidence: 99%